(3GdJgPjH aj JaSjQ GdbQBf GdcQjes - (3GdMSf Hf cQGeI GdLTej GdHjgbj, CHh SYjOs
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3dCfg GSe eGde jSe aGYdg aCeG ef bGd CQGO ZjQ GdeZVhH aMPa JhSYkG aZjQ UMM dCfg HefRdI GdaYd GdeJbOe s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3hdPdc bGd hbVi GdCeQh gPG GdGjdjb EdG HGdGNQI , (B,(3JOd Ydi Efg JYGdi eG jJge HeG hYOhG ajHWd bhd ef JLhR GdNda ai GdhYjO s
(3cJH Ydi Chd GdLRA GdKGfi HQSe GdTjN GdCLd fLe GdOjf GNJjGQ Gdedhc hGdSdGWjf jhSa Hf GdYaja Hf efja Hf Ydi Hf jYaQs
(3jHOC Chd GdeNWhW HJaSjQ ShQI GdaGJMIhBNQg HShQI GdHbQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YfjRI GdhWfjI HGdLGeY GdcHjQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs